Implementasi Dukungan Orang Tua dan Guru dalam Membangun Karakter Anak - Sembiring, Jenita Anjani Br (Universitas Nusantara PGRI Kediri, 2021)
At this time in the world of education often have difficulty in dealing with character development in students. This also reflects the erosion of noble values that are basically inherent in the child himself. The rapid advancement of technology is also suspected to be the cause of the erosion of the character value itself. It is fitting that with these technological advances, precisely in this era of globalization, as users of technology itself, we should be able to take advantage of this in developing our knowledge. But in reality there are still many users of this technology, in this case students who are less wise in using the technology. This also happened in one of the schools, namely the Private Junior High School of Santo Xaverius 2 Kabanjahe. Moving on from these problems, as for one of the methods used to develop the character and noble values inherent in students, cooperation is needed between the roles of parents and educators in building character so that they can create a generation that is competitive, open-minded, and has good character. The objectives of this study are: (1) To provide an overview of the conditions for the growth of the character of students. (2) Provide input for parents and teachers in building children's character. The data processing techniques obtained are by conducting field observations and constructive interviews with related parties.